PENGARUH PEMBELAJARAN INKUIRI BERBASIS PRAKTIKUM TERHADAP HASIL BELAJAR SISWA - Hafsemi Rapsanjani; Rizki Adri Yohanes; Fredy Fredy (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
This research is aimed at finding out the influence of Inquiry Learning Based Practice, to ward student’s study result in learning physic class X of SMAN 2 Gerung. The research was used experimental design. The population of the research was whole students class X which total number 123 students. Sample of the research was us random sampling technique and gotten class X1 and X3 as experimental and control group with sample 30 for experimental and 31 for control group. The data gathering was used objective test. Based on the results of the pre-test data analysis, the average value of the experimental class was 51.40 and that of the control class was 56.60. Post-testt results showed an average of 75.70 for the experimental class and 61.25 for the control class. The data analysis is used t-test formulation. Based on the data analysis is gotten that t-test is greater than t-table (6.49 greater than or equal to 2.019) with signification level 5%. It means that alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. Therefore, it taken conclusion that there is the influence of Inquiry Learning Based Practice, to ward student’s study result in learning physical class X of SMAN 2 Gerung.